Self-association of trimethylguanosine synthase Tgs1 is required for efficient snRNA/snoRNA trimethylation and pre-rRNA processing - Boon, Kum-Loong; Pearson, Michael; Koš, Martin (Scientific reports, 2015)
Trimethylguanosine Synthase catalyses transfer of two methyl groups to the m7G cap of RNA polymerase II transcribed snRNAs, snoRNAs and telomerase RNA TLC1 to form a 2,2,7-trimethylguanosine cap. While in vitro studies indicate that Tgs1 functions as a monomer and the dimethylation of m7G caps is not a processive reaction, partially methylated sn(o)RNAs are typically not detected in living cells. Here we show that both yeast and human Tgs1p possess a conserved self-association property located at the N-terminus. A disruption of Tgs1 self-association led to a strong reduction of sn(o)RNA trimethylation as well as reduced nucleolar enrichment of Tgs1. Self-association of Tgs1p and its catalytic activity were also prerequisite to bypass the requirement for its accessory factor Swm2p for efficient pre-rRNA processing and snRNA trimethylation. The ability to self-associate might enable Tgs1 to efficiently dimethylate the caps of the targeted RNAs in vivo.